Nagmaalviering in die NG Kerk - tussen tradisie en vernuwing. Deel 2 - Wepener, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
In this article, part 2 of our series, the historical survey of the celebration of the Lord’s Supper in the Reformed tradition is continued. Where the previous article focussed on Europe, especially Calvin and the Netherlands, this article focuses on South Africa and the Reformed world. Firstly the celebration of the Lord’s Supper in the history of the Dutch Reformed Church in South Africa is described. Secondly the influence of the Liturgical Movement as well as the World Council of Churches’ Faith and Order text, Baptism, Eucharist and Ministry, on the celebration of the Lord’s Supper is examined. A third part explores the practices surrounding the Lord’s Supper in the larger Reformed world, specifically in relation to frequency, forms, acts, preparation, ministers and three examples of how the sacrament is currently being celebrated in other Reformed churches. Finally the possibility of the implementation of new ways for celebrating the Lord’s Supper within the liturgy of the Dutch Reformed Church is explored. In Part 3 of our series on the Lord’s Supper, we will, building on the first two parts of our series, give practical theological criticism of and suggestions for the current situation regarding the celebration of the Lord’s Supper in the Dutch Reformed Church.